Wind farms reduce grassland plant community diversity and lead to plant community convergence - Xuancheng Zhao; Fengshi Li; Yuan Yuan; Guna Ari; Yongzhi Yan; Qing Zhang; Aruhan Olhnuud; Pengtao Liu (BMC Ecology and Evolution)
Abstract Climate warming has become a hot issue of common concern all over the world, and wind energy has become an important clean energy source. Wind farms, usually built in wild lands like grassland, may cause damage to the initial ecosystem and biodiversity. However, the impact of wind farms on the functional diversity of plant communities remains a subject with unclear outcomes. In this study, we chose 108 sample plots and identified 10 plant functional traits through a field vegetation survey. We used general linear regression analysis to assess how wind farm influenced vegetation community diversity, focusing on ten distinct plant functional traits. The study revealed that wind farm had significant impacts on grassland plant communities, diminishing diversity and functional traits, which leads to species composition convergence. Additionally, wind farm increased certain functional traits, like height and leaf area, while decreasing phosphorus content. Furthermore, the productivity of these plant communities was reduced by wind farm presence. This study highlights the negative consequences of wind farms in Inner Mongolia on plant diversity, aiming to offer scientific recommendations for the optimal arrangement of wind farms to safeguard biodiversity.